Kapasitas Mekanik Panel Komposit Beton Ringan terhadap Beban Siklik - Fatriady, M.R.; Djamaluddin, R.; Tjaronge, M.W.; Amiruddin, A.A. (Tadulako University, 2024)
The position of our country is included in the area Ring of Fire, where 90% of earthquakes on earth will occur in this region. Earthquakes in West Sumatra (2009), Mentawai (2010), Lombok and Palu (2018) have claimed more than 10,339 lives and more than 100,000 heavy damage to buildings. Building walls are generally made of brick or adobe, but these two materials have several disadvantages including weight and brittle. As a result of its considerable weight, it will increase the dead load of the structure so that the earthquake load will also increase. Thus, lightweight and clay materials (ductile) will be better if used as earthquake-resistant building walls and the level of risk is lower. Prefabricated sandwich panels produced by PT. BUILDING TECHNOLOGIES INDONESIA within BUKAKA TEKNIK UTAMA Tbk Group. to be a series of cyclic load tested full scale wall constructions. The conventional panel circuit model obtained the behavior of each swaying wall segment as an independent individual panel. Cyclic test results up to drift 12 were obtained with a maximum load of 4.245 kN with a maximum displacement of 106.28 mm compressive direction and a maximum load of 1.425 kN with a maximum displacement of 75.68 mm pulling direction. Deviation behavior is obtained that continues to increase as horizontal loads increase, but not until structural damage occurs in the series of 3 sandwich walls. This condition is a positive thing in the development of buildings with light materials to reduce the magnitude of the earthquake force and minimize damage and casualties.